PENGEMBANGAN MODEL KONSTRUKSI GARASI FIRE STATION DI BANDAR UDARA ADI SOEMARMO BOYOLALI - Wibowo, Anugrah rangga; Nunuk Praptiningsih; Nawang Kalbuana (Universitas Lampung, 2025)
Airports are required to have reliable Aircraft Rescue and Fire Fighting (ARFF) facilities as part of aviation safety systems. The fire station garage is a vital facility to protect firefighting vehicles and support rapid response in emergencies. The garage at Adi Soemarmo Airport in Boyolali currently faces issues such as an excessively high roof, water pooling on the floor, and operational disturbances caused by bird droppings. This study aims to design a more effective garage construction model that complies with safety standards. The method used is Research and Development (R&D) with four stages: identifying potential and problems, collecting data, design development, and expert validation. Data were obtained through observation, interviews, and documentation. The result is a garage design that can prevent rainwater splashing, has an optimal drainage system, and improves ARFF personnel comfort and work efficiency. This design is expected to be a practical technical solution to support safer airport operations.